Gummy smile correction with botulinum toxin type A (Research, Society and Development, 2023)
The harmonious smile is characterized by a balanced facial expression, where the teeth, lips and gums are in proper proportion, creating a natural and pleasing appearance. In contrast, gummy smile (GS) is characterized by excessive gingival exposure when smiling, which can be considered unwanted and cause embarrassment to the patient. Botulinum toxin type A (TXBA) has proven to be an effective and safe therapeutic option to correct GS, reducing gingival exposure while smiling. The procedure is minimally invasive and temporarily blocks the muscle activity responsible for the exaggerated lifting of the upper lip. In addition to improving smile aesthetics, the application of TXBA also contributes to patients' self-esteem and quality of life. The orofacial harmonization approach, focusing on the proper application of TXBA, promotes remarkable results, restoring patients' confidence and improving their well-being, making it a popular option in cosmetic dentistry. The treatment must be carried out by qualified professionals and personalized for each patient, guaranteeing natural and satisfactory results in the correction of the GS. Thus, the objective of the narrative review of the literature is to analyze and synthesize the scientific evidence available on the use of TXBA in the treatment of GS, focusing on reducing excessive exposure of the gingiva during smiling.